PENILAIAN KINERJA KARYAWAN DI ITENAS DENGAN MENGGUNAKAN METODE SAW BERBASIS WEBSITE - I Putu Eka Warmayudha; Komarudin Komarudin (STMIK Mardira Indonesia, Bandung, 2019)
In order to improve the quality of human resources performance, usually performed performance appraisal of human resources. This performance appraisal refers to several aspects of the assessment that have been determined by the institution. Performance appraisal criteria generally include aspects of discipline, the ability to perform tasks, attitudes and behaviors in the workplace, cooperation and some other aspects that have been determined. Seeing the number of employee performance appraisal criteria that exist in Itenas Bandung required a system that can help the human resources bureau in the assessment. The system required under these conditions is a decision support system. One method that can be used in this performance appraisal system is the SAW (Simple Additive Weighting) method. The calculation result with SAW method is suitable to solve the problem of calculation of performance appraisal result of employee because result obtained according to system that is running. The built-in decision support system application can help generate the employee performance appraisal report automatically. Key Word : Employee Performance Assesment, Itenas, SAW MethodDOI : http://doi.org/10.5281/zenodo.3631059